Evaluation in health promotion: thoughts from inside a human research ethics committee. (5th November 2015) - Allen, Judy; Flack, Felicity
Abstract : Health promotion research, quality improvement and evaluation are all activities that raise ethical issues. In this paper, the Chair and a member of human research ethics committees provide an insiders' point of view on how to demonstrate ethical conduct in health promotion research and quality improvement. Several common issues raised by health promotion research and evaluation are discussed including researcher integrity, conflicts of interest, use of information, consent and privacy.